Can Previous Levels of Physical Activity Affect Risk Factors for Cardiorespiratory Diseases and Functional Capacity after COVID-19 Hospitalization? A Prospective Cohort Study - Viana, Ariane Aparecida [UNESP]; Heubel, Alessandro Domingues; Do Amaral, Vanessa Teixeira [UNESP]; Linares, Stephanie Nogueira; De Oliveira, Gustavo Yudi Orikassa [UNESP]; Martinelli, Bruno; Borghi Silva, Audrey; Mendes, Renata Gonçalves; Ciolac, Emmanuel Gomes [UNESP] (Wiley, 2022)
Purpose. To evaluate the influence of previous levels of physical activity on hemodynamic, vascular, ventilatory, and functional outcomes after coronavirus disease 2019 (COVID-19) hospitalization. Methods. Sixty-three individuals with COVID-19 had their clinical status and previous levels (12 month) of physical activity (Baecke Questionnaire of Habitual Physical Activity) assessed at hospital admission. Individuals were then allocated to lower levels of physical activity (ACTLOWER; N=22), intermediate levels of physical activity (ACTINTERMEDIATE; N=22), or higher levels of physical activity (ACTHIGHER; N=19) groups, according to tertiles of physical activity. Resting hemodynamic (heart rate and brachial/central blood pressures) and vascular (carotid-femoral pulse wave velocity, augmentation index, and brachial artery flow-mediated dilation) variables, pulmonary function (spirometry), respiratory muscle strength (maximal respiratory pressures), and functional capacity (handgrip strength, five-time sit-to-stand, timed-up and go, and six-minute walking tests) were measured at 30 to 45 days after hospital discharge. Results. ACTLOWER showed lower levels (P<0.05) of forced vital capacity, forced expiratory volume in the first second, maximal voluntary ventilation, and maximal expiratory pressure than ACTHIGHER. ACTLOWER also had lower (P=0.023) walking distance (21%,) and lower percentage of predicted walking distance (20%) at six-minute walking test during follow-up than ACTINTERMEDIATE. However, hemodynamic and vascular variables, handgrip strength, five-time sit-to-stand, and timed-up and go were not different among groups. Conclusion. ACTLOWER showed impaired ventilatory parameters and walking performance when compared with ACTHIGHER and ACTINTERMEDIATE, respectively. These results suggest that previous levels of physical activity may impact ventilatory and exercise capacity outcomes 30 to 45 days after COVID-19 hospitalization discharge.